Quality of design and usability: a vetruvian twin - Voordt, Theo J. M. van (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2009)
This paper explores different indicators of quality of architectural design that are used in debates and design appraisals in the Netherlands. In addition to the old Vitruvian trilogy of utilitas, firmitas and venustas, a plea is made for a broad view on quality of architectural design. Because buildings go far beyond “free art”, in particular usability and the user’s point of view should be one of the issues to include in design quality indicators. The theoretical framework of quality indicators has been used to reflect on the criteria that were applied to select the architect of the new Deventer Town Hall plus library. A comparison of theory and practice shows that an integral multi-criteria quality assessment, personal preferences and interests, and practical constraints such as limited time, money and information are at odds. At the same time integrated assessments of designs (ex ante) or buildings-in-use (ex post) are essential to build up a body of knowledge on how to synthesize form, function and construction within the boundaries of project constraints.